2019
DOI: 10.1029/2019gl082850
|View full text |Cite
|
Sign up to set email alerts
|

Phased Response of the Subpolar Southern Ocean to Changes in Circumpolar Winds

Abstract: The response of the subpolar Southern Ocean (sSO) to wind forcing is assessed using satellite radar altimetry. sSO sea level exhibits a phased, zonally coherent, bimodal adjustment to circumpolar wind changes, involving comparable seasonal and interannual variations. The adjustment is effected via a quasi‐instantaneous exchange of mass between the Antarctic continental shelf and the sSO to the north, and a 2‐month‐delayed transfer of mass between the wider Southern Ocean and the subtropics. Both adjustment mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…This suggests that the variability in barotropic transport is indeed connected with remote forcing. In fact, Naveira Garabato et al (2019) has already shown the connection between sea‐level anomalies and circumpolar winds and our results support their discussion with in situ observations. Also, the correlation between barotropic flow and surface stress is valid, regardless of whether or not sea ice concentration/velocity were accounted for in the method used to calculate the surface stress.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the variability in barotropic transport is indeed connected with remote forcing. In fact, Naveira Garabato et al (2019) has already shown the connection between sea‐level anomalies and circumpolar winds and our results support their discussion with in situ observations. Also, the correlation between barotropic flow and surface stress is valid, regardless of whether or not sea ice concentration/velocity were accounted for in the method used to calculate the surface stress.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we provide a fit-for-purpose seasonal climatology of the subpolar Southern Ocean and propose two ASF proxies to fill this gap. Beyond representing an important benchmark for the evaluation of the ocean and climate models in this critical part of the world, our results are timely and complementary to the validation and usage of the currently growing development of satellite altimetrybased products of sea surface height in the sea ice sectors, which will undoubtedly bring an important new sight on ASF dynamics in the coming years (Armitage et al 2018;Dotto et al 2018;Naveira Garabato et al 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the lower‐frequency variability in the barotropic velocities decreases with the presence of sea ice, suggesting that atmospheric forcing is (at least in part) important. The low‐frequency variability could be related to wind‐driven changes on the continental slope, either linked to local winds (Dotto et al., 2019) or large‐scale wind forcing (Naveira Garabato et al., 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%